Evaluation of the Quality of YouTube Videos for Age-related Macular Degeneration in Turkey - Mine Ozturk; Ibrahim Cagri Turker; Gurcan Dogukan Arslan (Haseki Tıp Bülteni)
Aim: Patients frequently use YouTube for information. This study aimed to evaluate the quality of Turkish YouTube videos on age-related macular degeneration (AMD). Methods: Turkish translations of “AMD” and “yellow spot disease” were searched on August 16, 2023. The first 100 videos were grouped as useful, misleading, or irrelevant. Video properties and quality scores [Journal of American Medical Association (JAMA), Global Quality Score (GQS), DISCERN] were evaluated. Results: We classified 74 videos as useful, 16 as misleading, and 10 as irrelevant. The most common uploaders were television shows and social media. The mean JAMA score was 1.94±1.09, the mean GQS score was 2.49±1.29, and the mean DISCERN score was 36.82±16.53. The mean JAMA, GQS, and DISCERN scores were higher in the useful group than in the misleading group (p=0.0001, p=0.001, p=0.0001). The number of likes and view ratio were higher in the misleading group than in the useful group (p=0.019, p=0.037). The main content of the misleading group was treatment, and the uploaders were related to industry and commercial interests. Conclusion: The quality of the AMD videos was insufficient. Although misleading videos had lower quality, they were more popular. This may be due to patients’ hope for new treatments, as misleading videos have discussed this topic.